Pengembangan desa wisata zona B di Desa Gilangharjo, Kabupaten Bantul - Binarti, Floriberta; Ardhiansyah, Nicolaus Nino; Liauw, Adrian Hansen; Chandramaya, Steven (Jurnal Atma Inovasia, 2023)
The design of organic paddy fields and Gunung Cilik tourist areas is a part of Gilangharjo Village tourism development based on community empowerment (CBT). The tourist facilities provided in the area were designed to preserve local wisdom and ecological principles included as characteristics of CBT. The preservation of local wisdom was manifested through applying Bantul's distinctive architectural style and using local materials and vegetation. The ecological principles were applied through a temporary stage system, efficient material building design, high albedo materials, and porous paving. This design hopefully can empower the local community to the maximum extent, preserve local wisdom, and increase tourism visits without harming the environment.